Scarce Water in Site: A Content Analysis of News Coverage of the Sites Reservoir Project - Cara Lawson; Richard Austin-Castillo; Lauren Chase (Journal of Applied Communications, 2023)
Plagued by recent and historic drought, the need for water storage and management solutions in California is apparent. As a potential solution, the Sites Reservoir project offers an opportunity to a state eager to conserve and better manage water. The Sites Reservoir project involves complexities from a variety of standpoints and stakeholder perspectives. This study investigated the frames and sources used by The Sacramento Bee to communicate about the Sites Reservoir project over a 10-year period. The most frequently used frames throughout the dataset were “policy and government” and “water conscious,” and the sources most frequently utilized for information about the project in the articles were elected officials, government agency representatives, and nonprofit representatives. The findings suggest water management is linked with political activities and supports the assertion that the media tend to focus on the role of policy and political opinion in water management issues. At the same time, the findings suggest the need for water solutions is evident, given the prominence of the “water conscious” frame. Future studies should evaluate frames over time, and investigate the potential nuance between frames used to communicate about water management in different areas of the United States facing water management issues.
Keywords: framing; sources; water conservation; water management